Report on sampling leaf tissue, DNA extraction and prepare for shipment for genotyping of two biparental populations to identify QTLs associated with Spittlebug resistance - Espitia, Paula A.; Hernández, Luis Miguel; Villegas, Daniel Mauricio; Arango, Jacobo; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2021)
Spittlebugs (Hemiptera: Cercopidae) are the major production limitation for Brachiaria grasses (Urochloa spp.) in the tropical America. Incorporate host-plant resistance to new hybrids is the most cost-effective and sustainable solution to overcome the great losses caused by this key pest. Identifying regions in Urochloa genome associated with resistance to Aeneolamia varia nymphal attack, would allow to develop genotyping tools (e.g., molecular markers) that contribute to the hybrid’s selection in Urochloa interspecific breeding pipeline. Leaf tissue was extracted from 315 genotypes from the three biparental populations constructed for QTL analysis. These samples are kept at -20ºC, to be lyophilized and shipped for genotyping through RAD sequencing.